2020
DOI: 10.1002/car.2592
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Perspective on the Relationship between Child Sexual Abuse and Depression: A Systematic and Meta‐Analytic Review

Abstract: It is essential to examine child sexual abuse (CSA) and depression from a developmental perspective. Two meta‐analyses were conducted to examine the relationship between CSA and depression pertaining to the age at onset. English and Chinese databases were searched for articles on the association between CSA and depression that were published before December 2016. Random effect models were used in the meta‐analyses (35 studies with 37 effect sizes altogether). The result of the first analysis showed that CSA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 81 publications
2
11
0
3
Order By: Relevance
“…‘CSA experience is significantly related to an earlier onset of depression [among adult patients with depression] with a moderate effect size … which suggested that sexually abused patients were generally more likely to develop depression at an earlier age.’ (Li et al ., , p. 34)…”
Section: Systematic Reviews and Csamentioning
confidence: 96%
See 4 more Smart Citations
“…‘CSA experience is significantly related to an earlier onset of depression [among adult patients with depression] with a moderate effect size … which suggested that sexually abused patients were generally more likely to develop depression at an earlier age.’ (Li et al ., , p. 34)…”
Section: Systematic Reviews and Csamentioning
confidence: 96%
“…The first meta‐analysis sought to examine the relationship between CSA experiences and the age at onset of depression. These researchers found that:
‘CSA experience is significantly related to an earlier onset of depression [among adult patients with depression] with a moderate effect size … which suggested that sexually abused patients were generally more likely to develop depression at an earlier age.’ (Li et al ., , p. 34)
Their meta‐analysis was based on 13 papers with a total of 8652 patients with depressive disorders. They also found that the only significant moderating relationship was gender, with studies having more females in them reporting larger effect sizes.…”
Section: Systematic Reviews and Csamentioning
confidence: 99%
See 3 more Smart Citations